Device interference ability and link stability based on multi-devices cooperation and maintenance mechanism - Jie ZHANG; Lan-lan RUI; Shao-yong GUO; Xue-song QIU; Yi-fan DING (Tongxin xuebao)
To reduce costs of cooperation solutions maintenance and meet certain demand of service quality,a multi-devices cooperation and maintenance mechanism (MDCMM) based on device interference ability and link stability was proposed.With amulti-devices cooperation model,and an evaluation index considering both the heterogeneous device interference ability and the link stability,MDCMM provides a maintenance mechanism of the ubiquitous service in a certain period based on dynamic planning optimization strategy,aims at reduces interference of cooperation solutions switching and meet users’ diverse needs.Simulation results show that,compared with the existing mechanism,MDCMM has lower maintenance costs,smoother cooperation solutions,and better able to guarantee the user experience.